THE ECONOMIC VALUE OF HYDROLOGICAL SERVICES IN MENDALAM SUB WATERSHED, KAPUAS HULU REGENCY, WEST KALIMANTAN, INDONESIA - Emi Roslinda; Yuliantini Yuliantini (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2014)
Forest ecosystem supports almost all of the needs of human being through its contribution of tangible and intangible values. Currently, the intangible values have gained less attention than the tangible values that cause underestimation of the total value of the forest conversion into other more tangibly profitable usages, and miss-management of the forest. One of the important intangible values is the hydrological value that has been hardly calculated until now. This research the intangible values of water for household, transportation, agriculture and fishing in Mendalam Sub Watershed, Kalimantan. The economic values calculated based on market prices, opportunity costs and consumer’s surplus methods. The results showed that based on the opportunity cost method the economic values of the hydrological services was about Rp 8,043,706,237.50 per year. Meanwhile, the economic values of the hydrological services based on the consumer’s surplus method gave lower value than the former method, i.e. Rp 8,031,351,664.60 per year. This study showed that the economic value of the hydrological services was very high, which has not been included in the calculation yet. However, without trees there would be no forest and all other values included water value would not exist. Consequently, current forest management should put forest ecosystem as important to consider.